Xanthurenic Acid Formation from 3-Hydroxykynurenine in the Mammalian Brain: Neurochemical Characterization and Physiological Effects. (26th December 2017) - Sathyasaikumar, K.V.; Tararina, M.; Wu, H.-Q.; Neale, S.A.; Weisz, F.; Salt, T.E.; Schwarcz, R.
Highlights: The neosynthesis of xanthurenic acid (XA) from 3-hydroxykynurenine (3-HK) was examined in mice, rats and humans. In all 3 species, XA formation from 3-HK was traced to a major role of kynurenine aminotransferase II (KAT II). In slices from rat hippocampus, both 3-HK and XA reduced the slopes of dentate gyrus field EPSPs. Endogenous XA, newly formed from 3-HK, may play a physiological role in attentional and cognitive processes. Abstract: Xanthurenic acid (XA), formed from 3-hydroxykynurenine (3-HK) in the kynurenine pathway of tryptophan degradation, may modulate glutamatergic neurotransmission by inhibiting the vesicular glutamate transporter and/or activating Group II metabotropic glutamate receptors. Here we examined the molecular and cellular mechanisms by which 3-HK controls the neosynthesis of XA in rat, mouse and human brain, and compared the physiological actions of 3-HK and XA in the rat brain. In tissue homogenates, XA formation from 3-HK was observed in all three species and traced to a major role of kynurenine aminotransferase II (KAT II). Transamination of 3-HK to XA was also demonstrated using human recombinant KAT II. Neosynthesis of XA was significantly increased in the quinolinate-lesioned rat striatum, indicating a non-neuronal localization of the process. Studies using rat cortical slices revealed that newly produced XA is rapidly released into the extracellular compartment, and that XA biosynthesis can be manipulated experimentally in the same way as the production of kynurenic acid from kynurenine (omission of Na + or glucose, depolarizing conditions, or addition of 2-oxoacids). The synthesis of XA from 3-HK was confirmed in vivo by striatal microdialysis. In slices from the rat hippocampus, both 3-HK and XA reduced the slopes of dentate gyrus field EPSPs. The effect of 3-HK was reduced in the presence of the KAT inhibitor aminooxyacetic acid. Finally, both 3-HK and XA reduced the power of gamma -oscillatory activity recorded from the hippocampal CA3 region. Endogenous XA, newly formed from 3-HK, may therefore play a physiological role in attentional and cognitive processes.